supposed that A and B are independent events such that the probability that neither occurs is a and the probability of B is b. show that P(A) =(1- b-a) /(1-b)
supposed that A and B are independent events such that the probability that neither occurs is a and the probability of B is b. show that P(A) =(1- b-a) /(1-b)
You know that if A and B are independent events so are A' and B' are independent events.
$\displaystyle a=P(A'\cap B')=P(A')P(B')=(1-P(A))(1-P(B))=(1-{\color{blue}P(A)})(1-b)$
Now solve for $\displaystyle {\color{blue}P(A)}$